A Bibliometric Analysis and Literature Review of Sustainable Business Practices: Sustainability Disclosure in Indonesia’s Cement Industry - Wijaya Triwacananingrum; Rahmawati Rahmawati; Djuminah Djuminah; Agung Nur Probohudono (Journal of Law and Bibliometrics Studies, 2027)
Objective: The purpose of this study is to analyze data mapping from cement companies and disclosures in sustainability reports. Diagrams will be incorporated to facilitate a comprehensive understanding. Method: This research uses sustainability reports from 17 cement companies in Indonesia, with disclosure years 2017-2020, using the GRI standards approach. This study reviews sustainability reports using Textual Analysis with a word-count approach developed by Loughran and McDonald. This approach counts how many words describe the context of the sustainability report and its disclosures, followed by the presentation of the Bibliometric Analysis developed by Hesford. Furthermore, the researcher will conduct a complete descriptive and thematic analysis. Results: This study shows that Semen Jawa had the best overall sustainability disclosures across the observed years. The most general aspect was disclosed by Semen Jawa in 2017, Semen Tonasa in 2018, and Semen Baturaja in 2019 and 2020. The most economical aspect was Semen Jawa throughout 2017-2019, and Semen Baturaja in 2020. Disclosing the most environmental aspect was PT. Indocement Tunggal Perkasa for the entirety of the observed years. The most social aspect was Semen Jawa from 2017-2020. With this mapping, you will be able to see the cement industry's concern for sustainability. Novelty: Through sustainability reports, it is hoped to demonstrate the sustainability of Indonesia's cement industry, which is expected to help protect it from the negative impacts of its production operations. Therefore, it is hoped that the cement industry's role in the country's economy will eventually be strengthened.